Moralna ocena sztucznej prokreacji - Malina, Lucyna (Studia Pastoralne, 2020)
Article presents the techniques of artificial procreation and their moral evaluation. It is a problem, first of all, of conceiving a child outside the mother’s body. Main technique of artificial procreation is the in vitro method. Other problems associated with artificial procreation are the creation of supernumerary embryos, hyperstimulation of ovaries for the production of ova, and the use of masturbation to obtain sperm. Other activities include cryopreservation of supernumerary embryos or the use of the institution of a surrogate mother. Particular danger connected with in vitro method is human cloning, not only for reproductive purposes. In addition, methods of artificial procreation do not support, but replace the marital act. Due to the above-mentioned reasons, these methods can not be considered morally decent. This is the position of the Catholic Church.